Assessing the People’s Access to Public Spaces in Indian Cities: A Case of Bhubaneswar - Amit Kumar Biswal; Preeti Onkar (Calibrating Urban Livability in the Global South, 2024)
The last couple of decades in India has been truly a time of urbanization as most of the urban areas have doubled in size with massive migrations from rural India. This trend has simultaneously presented urban India with a new set of challenges, with limited resources maintenance and usage became quite challenging and critical. Land resources have been one of the major concerns and terms of sustainable utilization. The balance in land use pattern is crucial in creating a healthy and functional city, yet it was getting increasingly difficult to manage the existing land resources, especially in cities. Public spaces are one of the vulnerable land resources among these. Without the protection of these spaces, it is an easier target for housing sectors and industries to acquire. Historically India used to have ample amount of public gathering spaces in any type of settlement. Yet in recent years with growing urbanization public spaces at now not easily accessible to everyone. Bhubaneswar has an open space ratio of 2.7 square meters per head with a lot of people residing outside its reachable distance. The WHO recommends 9 square meters of public spaces per person and the UN recommends accessibility of such public spaces for users within a 10-minute walk which is approximately 800 m. Modern Indian cities often lack the required public open spaces in an effective range to reach these parameters. This study tries to evaluate the current scenario of available public spaces in a two-pronged approach. Evaluating how many people can access the space, with GIS-based spatial mapping and using isochrone tools to analyze the coverage of each public space, Identifying the gaps in the current scenario and also trying to build a survey-based scenario to understand the public perception. This parallel approach resulted in the visualization of 54% population of the city that can’t access public spaces while also providing information about people’s perspectives on which factors play crucial roles in creating a walkable neighborhood to make the public spaces more accessible.